The Role of Teachers in Improving Quality of Education and Developing Competencies of Primary School Students at Muslim Suksa School Thailand - Sulastri, Asri; Adri, Helmia Tasti; Syamsudin, Didin (Pusdikra Publishing, 2024)
This research aims to investigate the role of teachers in improving the quality of education and developing the competencies of elementary school students (prathom) at Suksa Muslim School, Thailand. Good quality education and developing student competencies are key elements in creating an educated and developed society. This research was carried out from January to February 2023 at Muslim Suksa School, Thailand. This research uses qualitative methods by collecting data through observation, interviews and document analysis. Teachers at these schools are the subjects of research to understand the practices and strategies they apply to improve student quality and competency. The results of this research reveal that the teacher's role is very important in creating a conducive learning environment, motivating students, and facilitating effective learning. Teachers at Muslim Suka School, Thailand apply a variety of creative and diverse learning strategies, integrate values into lessons, and focus on students' comprehensive development. The findings of this research provide insight into best practices in primary education in schools based in Thailand. The implication of this research is that the role of teachers in developing student competencies is very important and can contribute to better quality education.